Technological Pedagogical Content Knowledge (TPACK) Prospective Biology Teachers in Distance Learning - Mega Elvianasti; Muthia Rahmadani; Meitiyani; Prima Mutia Sari (Indonesia Approach Education, 2023)
Although much research has been done on TPACK, there is still nothing that examines TPACK for potential distance learning teachers. This study aims to determine the TPACK ability possessed by prospective biology teachers in distance learning through three main aspects, namely Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK). The research method used is the quantitative descriptive method. Research subjects were determined using the purposive sampling technique. Data was collected through TK, CK, and PK observation sheets; distance learning videos for prospective biology teachers; lesson plans; assessment sheets; and documentation. The result of data analysis shows that the TK ability of prospective biology teachers is within good criteria with a percentage of 80%, the PK ability of prospective biology teachers is within good standards with a rate of 77.27%, and the CK abilities of prospective teachers are within good criteria with a percentage of 80.94%. So, it can be concluded that the three aspects of TPACK for prospective biology teachers are reasonable criteria. The highest interpretation is on the ability of TK, and the lowest performance is on the knowledge of PK. The findings of this study are recommended for universities, especially in developing the TPACK abilities of prospective teachers.